A Flexible Sulfur‐Graphene‐Polypropylene Separator Integrated Electrode for Advanced Li–S Batteries. (6th November 2014) - Zhou, Guangmin; Li, Lu; Wang, Da‐Wei; Shan, Xu‐yi; Pei, Songfeng; Li, Feng; Cheng, Hui‐Ming
<x xml:space="preserve">Abstract</x> A flexible Li–S battery based on an integrated structure of sulfur and graphene on a separator is developed. The internal graphene current collector offers a continuous conductive pathway, a modified interface with sulfur, and a good barrier to and an effective reservoir for dissolved polysulfides, consequently improving the capacity and cyclic life of the Li–S battery. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>